Making the struggle for climate jobs common—confessions from an activist professor - Ytterstad, Andreas (Frontiers in Communication, 2024)
Anybody who lives “in the know” of the climate crisis – and understands some of the systemic causes of the relentless expansion of fossil fuel excavation and combustion – feels enfeebled by the obvious questions of what to say and/or what to do, to change things for the better. It does matter what we say, but most of the wise things have already been said. Meanwhile, journalists covering climate summits flip-flops between speaking the truth about where we are with global warming and political realism. This perspective article is shaped as confessions from an activist professor, who has inhaled climate activism and exhaled thoughts on climate communication for the last 15 years. Noting how the Latin roots of communicare is “to make common”, the author argues that the school strikes of 2019 were the last time hope was genuinly felt across the globe, because they found meaningful action together. What can be made common now, within the fog from Gaza, the Ukraine war and the cost of living crisis ? Instead of “blowing up a pipeline”, the author suggests that climate jobs can break more spells of inaction for majority publics and help unleash and shape the broadest possible mass climate struggle